Estudo molecular das subunidades STAG1 e STAG2 das Coesinas, e um dos seus fatores regulatórios, PDS5B, em carcinomas de células escamosas de boca - Josiane Alves França (2016)
Cohesin complex is responsible for sister chromatid cohesion. STAG1/STAG2 are part of the complex, which is regulated by PDS5B. Alterations in these genes were described in tumors. PDS5B is a negative regulator of cell proliferation. We aimed to assess molecular alterations in these genes in oral squamous cell carcinoma (OSCC) and predict their expression by the expression of 84 cell cycle genes. In addition, we investigated if pds5b protein expression impacted ki-67 and p53 immunopositivity. We assessed LOH at STAG1 and STAG2 loci in 15 OSCC by using 3 polymorphic markers. Associations between the immunoexpression of PDS5B and KI-67 and P53 were tested in 62 samples. Differences between transcriptional levels of STAG1, STAG2 and PDS5B between OSCC and normal oral mucosa (NM) were evaluated by qPCR. A 84 cell cycle genes qPCR array was carried out OSCC samples and STAG1, STAG2 and PDS5B were independently used as response variables in multiple linear regression models. LOH was observed at all 3 markers in at least one sample. PDS5B, P53 and KI-67 were highly expressed and no association was found between PDS5B immunoexpression and KI-67 or P53 (p>0.05). OSCC and MN showed similar transcriptional levels of STAG1, STAG2 and PDS5B. STAG1 and CUL3 expression seem to be related (p=0.004). In conclusion, there is LOH at STAG1 and STAG2 loci in OSCC, but OSCC and MN showed similar transcriptional levels of STAG1, STAG2 and PDS5B. PDS5B immunoexpression in OSCC was high, but it was not associated with proliferation cell index.